Pengembangan Media Interaktif “Game Huruf” dalam Meningkatkan Keterampilan Literasi pada Anak Kelompok B di TK Dharma Wanita Persatuan 7 Sengguruh - Haryono, Sarah Emmanuel; Sarah Emmanuel Haryono; Maghfirotul Isnaini; Henni Anggraini (Universitas Nusantara PGRI Kediri, 2025)
Building reading literacy skills in children must start early, besides that the learning process needs to be presented with methods that are fun for children. This study aims to analyze the feasibility of developing interactive media “Game Huruf” in improving reading literacy skills in group B children at Dharma Wanita Persatuan 7 Sengguruh Kindergarten. This research and development uses the Research and Development (R&D) approach method. Data collection techniques using observation, interviews, questionnaires, and documentation. The data analysis method used involves qualitative and quantitative descriptions. Based on the results of validation from material experts obtained a number 87 with a percentage of 98.86% classified as “Very Feasible”. Meanwhile, the material expert obtained a score of 76 and a percentage of 100% classified as “Very Feasible”. Based on the limited scale and broad scale trials, the results showed that there were six children who had not shown their ability when arranging letters to become simple words (names of fruits) and there were still children who did not understand the relationship between the sound and shape of the letters. Meanwhile, the other six children were able to recognize various vowel to consonant letter symbols, arrange letters into simple words (such as the names of fruits), and understand the relationship between sounds and letter shapes.